The 2023 League of Legends World Championship (LoL Worlds) As a Strategic Instrument of South Korea’s Public Diplomacy - Jannah, Fidtria Ridatin; Jatmika, Muhammad Indrawan (LPPM Universitas PGRI Adi Buana Surabaya, 2026)
Abstract explains the core of the manuscript informatively and obviously, including the subject matter, proposed approach, and solution, and shows key findings and conclusions. Abstract using English. The number of words in the abstract is about 100-250 words, written in one paragraph; any unfamiliar terms should be written in italic. Font type and size are Times New Roman (Headings) 11 pt. Abstract was written in single-spaced, and the margin was narrower than the main text. Keywords need to be listed and reviewed, and the main terms underlying the conduct of the research. Keywords could be a single word or phrase. Keywords including 3-5 words or phrases. These keywords are required for computerization. Research and abstract title search made easy with these keywords